Family Experiences of Central American Refugees Who Overestimate Intergenerational Gaps - Merali, Noorfarah (Canadian Journal of Counselling and Psychotherapy, 2007)
The present study aimed to assess the role of perception in shaping family realities after immigration. Research participants included six Central American parent-adolescent dyads who perceived each other to be further apart in their acceptance of cultural change than indicated by their self-ratings of behavioural shifts towards Western norms. The parents and adolescents were interviewed individually about family relationships after migration. Three themes emerged from parents' interview responses: (1) the perceived erosion of familism, (2) parenting stress, and (3) taking back control. Adolescents’ interview responses revealed two themes: (1) family conflict and (2) attachment and dependency in family relationships. Implications for counselling are discussed.